PENGARUH PENAMBAHAN KARAGENAN TERHADAP KARAKTERISTIK PERMEN JELLY KULIT ANGGUR HITAM (VITIS VINIFERA) - Dian Rna Fajarini, Luh; Ekawati, I Gusti Ayu; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This study aims to determine the effect of thecarrageenan on the characteristics of grape skins jelly candy and to find the right carrageenan concentration to produce jelly candy with the best characteristics. The experimental design used was randomized block design by treatment with carrageenan concentration of 1.0%, 1.5%, 2.0%, 2.5%, 3.0% and 3.5%. The treatment was repeated as many as 3 repetitions then obtained 18 units of the experiment, the data obtained from the result research were analyzed by variance and if the treatment had an effect on the variable then continued with Duncan test. The results showed that the addition of carrageenan with a concentration of 2.0% was the best characteristic of grape skins jelly candy with 18.01%moisture content, 0.82%ash content, 2.62 mg/100g anthocyanin, 16.07% sugar reduction content, color liked, flavor grape skins medium and liked, texture very chewy and liked, strong sweet taste and rather liked and overall acceptance liked.